2012
DOI: 10.7314/apjcp.2012.13.9.4301
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Weekly Cisplatin Versus Triweekly Cisplatin with Radiotherapy in the Treatment of Cervical Cancer: A Meta-analysis Result

Abstract: Aims: To evaluate the adverse effect and survival outcome of weekly and triweekly cisplatin with radiotherapy in treatment of cervical cancer. Methods: After an extensive literature search between 1995-2011,we analyzed 7 studies to compare weekly cisplatin and triweekly cisplatin combined radiotherapy. Results: Our analysis established that weekly cisplatin has a lower risk of hematologic toxicity than triweekly cisplatin with concurrent radiotherapy in the treatment of cervical cancer. However, there were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…To be more precise, it appears that it is the chemotherapy that predominantly contributes to hematologic changes and radiotherapy that results in gastrointestinal and other toxicities. This argument is indirectly supported by the observations in the studies by Hu et al (2012) where it was found that the hematologic toxicity was less with weekly cisplatin (40mg/m 2 ) compared to triweekly cisplatin (75 mg/m 2 ) and that the other toxicities did not show any difference with the two regimens.…”
Section: Discussionsupporting
confidence: 75%
“…To be more precise, it appears that it is the chemotherapy that predominantly contributes to hematologic changes and radiotherapy that results in gastrointestinal and other toxicities. This argument is indirectly supported by the observations in the studies by Hu et al (2012) where it was found that the hematologic toxicity was less with weekly cisplatin (40mg/m 2 ) compared to triweekly cisplatin (75 mg/m 2 ) and that the other toxicities did not show any difference with the two regimens.…”
Section: Discussionsupporting
confidence: 75%
“…In order to analyze systematically which regimen is better, a meta-analysis has been conducted to compare differences between weekly and triweekly cisplatin arms. 11 Nevertheless, the studies evaluated in the research are not all randomized controlled trials (RCTs), along with 2 of the articles from different stages of the same study, which impairs validity and credibility of the result. Consequently, the aim of this study was to evaluate adverse effect and survival of 2 regimens more fully and precisely.…”
mentioning
confidence: 99%
“…95 The potential benefit of weekly versus 3-weekly cisplatin-based concurrent CTRT in LACC has also been investigated in 2 meta-analyses. 122,123 and a retrospective single-institution review. 124 The conclusions from these studies are blurred because of the inclusion of both singleagent cisplatin and mostly combination regimes in a triweekly arm and the inclusion of retrospective studies with adjuvant CTRT in patients postoperatively.…”
Section: Discussionmentioning
confidence: 99%